PEMODELAN DAN SIMULASI SALURAN MOTOR BAKAR TORAK DUA LANGKAH DENGAN ALIRAN GAS TAK TUNAK - Soelaiman, T. A Fauzi; Bachrun, Rachmat K; Mangaranap, Arthur M (Mesin, 2001)
A two-stroke engine is one of the commonly used energy conversion systems for transportation.The process inside the cylinder and the transport passages can be simulated with mathematical models with certain assumptions. In modeling and simulating a two-stroke engine, the flows in the passages are modeled as unsteady gas flows. The unsteady gas flows are important in a twostroke engine since they affect the intake and exhaust processes of the working fluid. The results of the simulation can be used for analyzing or tuning the intake and exhaust passages of a two-stroke engine. As an example, the program was applied for a two-stroke engine MK1.